PENDEKATAN KRIMINOLOGI DALAM PENANGGULANGAN TINDAK PIDANA KEKERASAN TERHADAP PEREMPUAN DI KOTA GORONTALO - Rizki Ekwanto, Endah; Ibrahim, Vicky (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
This study aims to examine the crime of violence against women in Gorontalo City through a criminological approach, as well as evaluate the effectiveness of its countermeasures by relevant officials and institutions. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observations, and documentation studies. The results show that the rate of violence against women has continued to increase in the last three years, dominated by cases of domestic violence, sexual violence, and psychological violence. The main causative factors include gender inequality, the influence of patriarchal culture, low education, and weak legal protection systems. The findings also show that services to victims have not been optimal due to limited resources and lack of synergy between institutions. Through a feminist and critical criminology approach, this study emphasizes the importance of cross-sectoral interventions oriented towards the prevention, protection, and recovery of victims. The recommendations are addressed to local governments and law enforcement to strengthen regulations, public education, and integrated victim-based services to create a safe and equitable environment for women.